1999
DOI: 10.1111/j.1439-0450.1999.tb01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Agar Gel Immunodiffusion Test, Enzyme‐linked Immunosorbent Assay and Western Blotting for the Detection of BLV Antibodies

Abstract: An indirect enzyme-linked immunosorbent assay (ELISA) for the diagnosis of bovine leukaemia virus (BLV) infection was developed and compared with the agar gel immunodiffusion test (ACID?. Western blotting (WB) was used as confirmatory test. ELISA and AGIDT had specificities that were comparable with that of WB, however, ELSA showed a higher sensitivity than AGIDT. The ELISA was useful for screening a large number of samples, whereas WB was important for detecting the antibody response against the individual BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
2
11
0
1
Order By: Relevance
“…Es de suma importancia utilizar pruebas de laboratorio confiables y con alta sensibilidad ya que los programas de control y erradicación del virus de la leucosis se van a basar en la detección de los animales seropositivos, para la toma de decisiones de eliminación, segregación o manejo de animales debido a que el diagnóstico de los animales infectados o con linfocitosis persistente solamente se puede realizar en el laboratorio (Dolz y Moreno, 1999;Dolz et al, 2015) Los análisis oficiales y aprobados por la Organización Mundial de Sanidad Animal comúnmente utilizados para detectar anticuerpos de LEB incluyen ensayo enzimático ligado inmunoabsorbente (ELISA) y la inmunodifusión en gel de agar (IGDA) (Dolz y Moreno, 1999;Toma et al, 1990;Gutiérrez et al, 2009;Andreolla et al, 2018). Es importante mencionar que, a pesar de sus falencias, la técnica ELISA ha sido considerada como la más adecuada para el diagnóstico y programas de control, especialmente porque presenta mayor sensibilidad que el IGDA que por su baja sensibilidad podría dejar pasar infecciones en hatos clínicamente normales y a pesar de haber sido por mucho tiempo el análisis utilizado por su simplicidad y confiabilidad (Dolz et al, 2015).…”
Section: Diagnósticounclassified
“…Es de suma importancia utilizar pruebas de laboratorio confiables y con alta sensibilidad ya que los programas de control y erradicación del virus de la leucosis se van a basar en la detección de los animales seropositivos, para la toma de decisiones de eliminación, segregación o manejo de animales debido a que el diagnóstico de los animales infectados o con linfocitosis persistente solamente se puede realizar en el laboratorio (Dolz y Moreno, 1999;Dolz et al, 2015) Los análisis oficiales y aprobados por la Organización Mundial de Sanidad Animal comúnmente utilizados para detectar anticuerpos de LEB incluyen ensayo enzimático ligado inmunoabsorbente (ELISA) y la inmunodifusión en gel de agar (IGDA) (Dolz y Moreno, 1999;Toma et al, 1990;Gutiérrez et al, 2009;Andreolla et al, 2018). Es importante mencionar que, a pesar de sus falencias, la técnica ELISA ha sido considerada como la más adecuada para el diagnóstico y programas de control, especialmente porque presenta mayor sensibilidad que el IGDA que por su baja sensibilidad podría dejar pasar infecciones en hatos clínicamente normales y a pesar de haber sido por mucho tiempo el análisis utilizado por su simplicidad y confiabilidad (Dolz et al, 2015).…”
Section: Diagnósticounclassified
“…Currently, however, ELISA [17] and the fluorescence polarization assay [18] are successfully used to detect specific antibodies against M. bovis. Serodiagnostics of bovine leukemia virus also include modifications of ELISA [19,20], immunodiffusion in agar gel, and immunoblotting [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although AGIDT is a simple and reliable procedure, it has a relatively low sensitivity, which might favor the occurrence of low-titer BLV infections in clinically normal herds [5]- [7]. This is of remarkable importance in herds which had been tested repeatedly for some time with AGIDT [8] [9]. Previous results showed that control based solely on low sensitivity precipitation assays might complicate the epidemiology of BLV by selecting animals which, although infected, do not produce detectable antibodies in AGIDT.…”
Section: Introductionmentioning
confidence: 99%